Analysis of Variables Affecting Customer Satisfaction Using Online Food Purchase Services with Multiple Linear Regression - Fuji Rahayu Wilujeng (Universitas Nahdlatul Ulama Surabaya, 2023)
The surge in popularity of online food delivery services across Southeast Asia is undeniable. Remarkably, in the year 2020, Indonesia emerged as the frontrunner in Gross Merchandise Value (GMV) for such services in the region, amassing an impressive GMV of 3.7 billion, surpassing its regional counterparts. This burgeoning trend is underpinned by a multitude of factors motivating individuals to embrace online food purchases, including time efficiency, an array of enticing and pragmatic offers, and an abundance of choices. Building upon this backdrop, this research endeavors to delve into the intricate web of variables that wield influence over consumer satisfaction within the realm of online food procurement. Employing the multifaceted approach of multiple linear regression, the study aims to uncover the mechanisms that underlie this pivotal relationship. The findings gleaned from this investigation are noteworthy. They highlight the substantial joint impact of the independent variables on the dependent variable. This assertion is substantiated by the remarkably minute significance value of F, which registers at an impressive 0.000, comfortably falling below the conventional threshold of 0.05. This statistical affirmation underscores the collective potency of the five dimensions of service quality, cohesively exerting a significant influence on the variable of customer satisfaction. Moreover, a granular examination of the individual impacts of each independent variable warrants’ attention, as gleaned from their respective 't' significance values. It is discernible that the variables of reliability and responsiveness, with significant values exceeding 0.005, exhibit limited individual impact on customer satisfaction. This discernment underscores that, when assessed in isolation, these two independent variables fail to manifest a statistically noteworthy effect on the overarching construct of customer contentment.